Pengaruh Customer Bonding Dan Event Marketing Terhadap Repurchase Intention Pada Konsumen Vapormania di Kota Medan - Aminullah, Eji; Mardhiyah, Ainun; Siregar, Onan Marakali (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2025)
This research uses a quantitative approach with an associative research type. The sampling technique applied was purposive sampling, with a total of 96 respondents. Primary data was collected through distributing questionnaires online using Google Form, while secondary data was obtained through literature review. The data analysis techniques used include validity test, reliability test, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The findings in this study indicate that customer bonding and event marketing have a significant influence, both partially and simultaneously, on the repurchase intention of Vapormania consumers in Medan City. The coefficient of determination test results indicate a fairly strong relationship between customer bonding and event marketing on repurchase intention, with a correlation coefficient (R) of 0.735. Based on the Adjusted R Square value, it is known that the Customer Bonding (X1) and Event Marketing (X2) variables are able to explain the Repurchase Intention (Y) variable by 53%, while the remaining 47% is influenced by other factors not analyzed in this study